A biological condition gradient for coral reefs in the US Caribbean Territories: Part I. Coral narrative rules. (May 2022) - Santavy, Deborah L; Jackson, Susan K.; Jessup, Benjamin; Gerritsen, Jeroen; Rogers, Caroline; Fisher, William S.; Weil, Ernesto; Szmant, Alina; Cuevas-Miranda, David; Walker, Brian K.; Jeffrey, Christopher; Bradley, Patricia; et al.
Highlights: BCG narrative rules provide traits to detect change in coral condition and biological integrity. BCG model provides a robust tool for coral reef condition assessment. Narrative BCG model translates technical results so public can understand and support decisions. Decision rules inform biocriteria for water quality and natural resource programs. Coral reef BCG informs appraisal with systematic, transparent, and reproducible approach. Abstract: As coral reef condition and sustainability continue to decline worldwide, losses of critical habitat and their ecosystem services have generated an urgency to understand and communicate reef response to management actions, environmental contamination, and natural disasters. Increasingly, coral reef protection and restoration programs emphasize the need for robust assessment tools for protecting high-quality waters and establishing conservation goals. Of equal importance is the need to communicate assessment results to stakeholders, beneficiaries, and the public so that environmental consequences of decisions are understood. The Biological Condition (BCG) model provides a structure to evaluate the condition of a coral reef in increments of change along a gradient of human disturbance. Communication of incremental change, regardless of direction, is important for decision makers and the public to better understand what is gained or lost depending on what actions are taken. We developed a narrative (qualitative) Biological Condition Gradient (BCG) from the consensus of a diverse expert panel to provide a framework for coral reefs in US Caribbean Territories. The model uses narrative descriptions of biological attributes for benthic organisms to evaluate reefs relative to undisturbed or minimally disturbed conditions. Using expert elicitation, narrative decision rules were proposed and deliberated to discriminate among six levels of change along a gradient of increasing anthropogenic stress. Narrative rules for each of the BCG levels are presented to facilitate the evaluation of benthic communities in coral reefs and provide specific narrative features to detect changes in coral reef condition and biological integrity. The BCG model can be used in the absence of numeric, or quantitative metrics, to evaluate actions that may encroach on coral reef ecosystems, manage endangered species habitat, and develop and implement management plans for marine protected areas, watersheds, and coastal zones. The narrative BCG model is a defensible model and communication tool that translates scientific results so the nontechnical person can understand and support both regulatory and non-regulatory water quality and natural resource programs.